PD-1 inhibitor combined with radiotherapy and GM-CSF in MSS/pMMR metastatic colon cancer: a case report - Yang, Jiabao; Xing, Pengfei; Kong, Yuehong; Xu, Meiling; Zhang, Liyuan (Frontiers in Oncology, 2023)
Patients with chemo-refractory metastatic colorectal cancer (mCRC) have poor prognoses. The application of programmed cell death protein 1(PD-1)/ programmed cell death ligand 1 (PD-L1) inhibitors encouragingly improved the survival of mCRC patients with microsatellite instability-high (MSI-H)/ mismatch repair-deficient (dMMR). Unfortunately, it was ineffective for mCRC with microsatellite-stable (MSS)/proficient mismatch repair (pMMR), which accounted for 95% of mCRC. Radiotherapy can promote local control by directly killing tumor cells and inducing positive immune activities, which might help synergistically with immunotherapy. We present the report of an advanced MSS/pMMR mCRC patient who had progressive disease (PD) after first-line chemotherapy, palliative surgery and second-line chemotherapy combined with targeted therapy. Then the patient received the therapy of PD-1 inhibitor combined with radiotherapy and granulocyte-macrophage colony-stimulating factor (GM-CSF). According to Response Evaluation Criteria in Solid Tumors version 1.1 (RECIST1.1), the patient showed a complete response (CR) after triple-combined therapy with progression-free survival (PFS) for more than 2 years so far. The patient had no other significant adverse reactions except for fatigue (Grade 1). The triple-combination therapy provided a promising strategy for metastatic chemo-refractory MSS/pMMR mCRC patients.